Validity and reliability of the Iranian preterm birth experiences and satisfaction scale: A methodological and cross-sectional study - Maryam Najjarzadeh; Sakineh Mohammad-Al; Shamsi Abbas-Alizadeh; Mohammad Asghari Jafarabadi; Mojgan Mirghafourvand; Nahid Tagipour-Amidi; Alexandra Sawyer; Susan Ayers (Tabriz University of Medical Sciences, 2021)
Background: Women's experience and satisfaction with childbirth care are increasingly being addressed by health care providers, managers, and policymakers. Due to need for a validated special scale for assessing satisfaction of women with preterm birth, we aimed to translate and adapt the first specific tool, Preterm Birth Experiences and Satisfaction Scale (P-BESS), into Persian language and evaluate its psychometric properties. Methods: A methodological and cross-sectional study was conducted in two tertiary levels of maternal hospitals in Tabriz. The Iranian version of the scale was developed from the original English version using forward-backward translation. After confirmation of its face and content validity, the scale was completed by 201 women who had given birth prematurely. Results: Exploratory factor analysis revealed three factors (staff professionalism and empathy, confidence in Staff, information and explanations) with eigenvalues greater than 1, explaining a total variance of 55.4%. Confirmatory factory analysis showed that the 17-item, three factor model fitted the data well: the root mean square error of approximation 0.060. There were moderate correlations between the total and sub-scales of Iranian P-BESS and overall satisfaction (r = 0.45 to 0.66), as well as need for improvement (r = -0.46 to -0.61), which confirm convergent validity. Internal consistency and test-retest reliability of the scale and its sub-scales were satisfactory (α = 0.852 to 0.922, intraclass correlation coefficient; 0.83 to 0.92). Conclusion: The Iranian version of P-BESS is a valid and reliable scale which can be used by policy makers, managers, health care providers and researchers.